Elles font l'abstraction - Macel, Christine; Ziębińska-Lewandowska, Karolina; Centre Georges Pompidou; Museo Guggenheim Bilbao (Éditions du Centre Pompidou, 2021)
Mise en lumière du rôle joué par les femmes artistes dans l'essor du courant de l'abstraction au XXe siècle à travers le monde. Les recherches personnelles ou en groupe de ces femmes sont présentées. Les spécialistes élargissent leurs propos à la danse, aux arts appliqués, à la photographie, au cinéma et aux arts performatifs. Avec les notices biographiques de 115 artistes.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cinéma; communication; cours; danse; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; performance; photographie; premier cycle; périodes historiques; thématiques

Postcolonial / Décolonial: la preuve par l'art - Toussaint, Evelyne (Presses universitaires du Midi, 2021)
Les liens entre art contemporain, histoire coloniale, postcolonialisme et mouvements décoloniaux sont anciens et multiples. Des artistes, en Occident et ailleurs, depuis plusieurs décennies déjà, revisitent opportunément des concepts que les études postcoloniales ont approfondis ou inventés - agency (agentivité), mimicry (mimétisme/simulacre) ou essentialisme stratégique -, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination. Des auteurs, relevant de ces champs d'études conservant aujourd'hui toute leur actualité politique, théorique et polémique, disent en retour tout l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art réunit des textes portant sur des productions artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, Iris Kensmil, Jean Renoir et bien d'autres), des propositions institutionnelles (Centro de Arte y Comunicación de Buenos Aires, Biennale de Venise ou Van Abbemuseum d'Eindhoven), l'historiographie de l'histoire de l'art ou celle du droit. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales–Page 4 de la couverture.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; droit; féminisme décolonial; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; science politique et droit; sciences de la gestion; thématiques; économie

Pour une esthétique de l'émancipation: construire les lignées d'un art queer - Alfonsi, Isabelle; Fraisse, Geneviève; Abonnenc, Mathieu K. (Mathieu Kleyebe) (B42, 2019)
"Loin de relire l'histoire de l'art en lui appliquant de façon anachronique le terme « queer », utilisé positivement dans les milieux militants depuis la fin des années 1980, Pour une esthétique de l'émancipation cherche à montrer comment l'écriture de l'Histoire de l'art a minoré l'importance des engagements politiques et affectifs des artistes et rendu inopérante la portée sociale de leurs œuvres. En imaginant des amitiés inédites entre des artistes du passé, Isabelle Alfonsi fait émerger une lignée féministe et queer pour l'art contemporain. Des pratiques artistiques du XXe siècle sont ainsi replacées dans le contexte du militantisme de défense des droits des homosexuel•le•s et de la formation d'une critique radicale féministe et anticapitaliste. Claude Cahun et Michel Journiac croisent l'histoire du minimalisme états-unien, vu à travers Lynda Benglis, Lucy Lippard ou Yvonne Rainer. Les guerres de représentation menées pendant la crise du sida sont lues au prisme des oeuvres de Felix Gonzalez-Torres, du concept de désidentification de José E. Muñoz et de l'activisme culturel du groupe Boy/Girl with Arms Akimbo, dans le San Francisco des années 1980."– Résumé de l'éditeur.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; activisme; approches et analyses; artistes queers; arts; cours; discipline; har4600; histoire de l'art; histoire et politique; militance; premier cycle; périodes historiques; queer; thématiques; émancipation

Archi-féministes!: art contemporain, théories féministes - Charron, Marie-Ève; Lafortune, Marie-Josée; St-Gelais, Thérèse; Optica (Galerie) (OPTICA, centre d'art contemporain, 2019)
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; queer; québec; régions géographiques; thématiques; études culturelles

Art & queer culture - Lord, Catherine; Meyer, Richard (Phaidon, 2019)
Spanning 125 years, Art and Queer Culture is the first major historical survey to consider the ways in which the codes and cultures of homosexuality have provided a creative resource for visual artists. Attempts to trouble the conventions of gender and sexuality, to highlight the performative aspects of identity and to oppose the tyranny of the normal are all woven into the historical fabric of homosexuality and its representation. From Oscar Wilde to Ryan Trecartin, from the molly houses of eighteenth-century London to the Harlem drag balls of the 1920s, the flamboyant refusal of social and sexual norms has fuelled the creation of queer art and life throughout the modern period. Although the book proceeds in a chronological fashion, it does not propose a progressive narrative in which homosexuals become increasingly adept at negotiating the circumstances of censorship and overcoming the terms of stigma and invisibility. The dialogue between art and queer culture does not move towards ever more affirmative images of equality and dignity. Rather than countering homophobia with 'positive' images of assimilation, many of the artists and photographers featured in this book draw upon, and even draw out, the deviant force of homosexuality. Art and Queer Culture includes not only pictures made and displayed under the rubric of fine art but also those intended for private, underground or otherwise restricted audiences. Scrapbooks, amateur artworks, cartoons, bar murals, anonymous photographs, activist posters, all appear in its pages, as do paintings, sculptures, art photographs and video installations. Writing queer culture into the history of art means redrawing the boundaries of what counts as art as well as what counts as history. It means searching for cracks in the partition that separates 'high' art from 'low' culture and in the divide between public achievement and private life
Première publication: 2013
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes queers; arts; cours; discipline; europe; fem1000; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; thématiques; états-unis

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Décolonisons les arts! - Cukierman, Leïla; Dambuy, Gerty; Vergès, Françoise (L'Arche, 2018)
"À l'initiative du collectif "Décoloniser les arts", Leila Cukierman, Gerty Dambury et Françoise Vergès analysent, avec quinze artistes, la colonialité à l'œuvre dans le monde des arts et de la culture en France et proposent des pistes pour une décolonisation des formations, des institutions et des contenus. Décolonisons les arts!, vaste et passionnant objectif, est abordé à partir de pratiques et de textes critiques qui étudient l'absence de formes de narrations prenant à rebours le récit national. L'ouvrage est une invitation à ouvrir le regard et à prêter l'oreille à la transversalité des récits, un appel à se rassembler pour transformer le champ culturel et artistique où la décolonisation vise à l'émancipation créatrice et à une nécessaire et urgente transformation du monde."–Page 4 de la couverture.
Keywords: approches et analyses; arts; cours; critique institutionelle; discipline; europe; france; féminisme décolonial; har4600; histoire de l'art; histoire et politique; premier cycle; régions géographiques; thématiques

Art queer: une théorie freak - Lorenz, Renate; Bortolotti, Marie-Mathilde; Alfonsi, Isabelle (B42, 2018)
Art queer s’intéresse à la façon dont les stratégies de dénormalisation mises en place par les arts visuels peuvent se prolonger par le biais de l’écriture. Dans les trois chapitres de ce livre, les discussions théoriques et artistiques s’associent à la théorie queer, aux études sur la handicap et à la théorie postcoloniale pour définir trois pratiques : le drag radical, le drag transtemporel et le drag abstrait. Une des caractéristiques de l’art queer, tel que le définit Renate Lorenz, est sa possibilité d’agir à travers le temps, désorganisant une chronologie positiviste et se saisissant d’objets historiques par affinité. L’art queer cultive l’anachronisme comme méthode. En s’appuyant sur le travail de onze artistes, le livre est moins une tentative de relecture de l’histoire de l’art, que la manifestation d’une méthode, que l’auteure nomme drag, qui rendrait apparents des modes d’assemblages, « des connections productives entre le naturel et l’artificiel, l’animé et l’inanimé, tout ce qui permet de produire des connections aux autres et aux choses plutôt que de les représenter ». Parmi les artistes étudié∙e∙s figurent notamment Zoe Leonard, Shinique Smith, Jack Smith, Wu Tsang, Ron Vawter, Bob Flanagan, Henrik Olesen, Felix Gonzalez-Torres, Sharon Hayes et Pauline Boudry/Renate Lorenz.
Keywords: abstraction; approches et analyses; art contemporain; arts; assemblage; cours; discipline; drag; har4600; histoire de l'art; histoire et politique; méthodologie; premier cycle; queer; thématiques; transtemporalité

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Au temps de l’homonationalisme: mythologie nationaliste et inclusivité LGBT - Glenn, Clinton (esse arts + opinions, 2017)
À travers cette rhétorique homonationale, l’exceptionnalisme canadien met en place tous les éléments pour récupérer la sexualité queer racisée (blanche et non blanche) selon un mode de gouvernance néolibéral faisant fi de la couleur en produisant des sujets citoyens queers exceptionnels et en affirmant le statut exceptionnel du Canada dans le monde.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; arts; canada; cours; discipline; har4600; histoire de l'art; histoire et politique; homonationalisme; identités LGBTQIA2+; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; thématiques; ville

Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Éditions Mimésis, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Artistes femmes: la parenthèse enchantée: XVIIIe-XIXe siècles - Sofio, Séverine (CNRS éditions, 2016)
Entre 1750 et 1850, l'univers des beaux-arts connaît de profondes mutations, dont l'une des conséquences est la banalisation d'une image positive de la dame artiste. Progressivement, des barrières s'abaissent, des contraintes se desserrent et la pratique de la peinture est rendue plus accessible aux femmes. S'ouvre alors une période de créativité foisonnante associée aux noms–parfois oubliés aujourd'hui–d'Elisabeth Vigée-Lebrun, Adélaïde Labille-Guiard, Marie-Guillemine Benoist, Marguerite Gérard, Constance Mayer, Victoire Jaquotot, Lizinka de Mirbel, Rosa Bonheur ...
Keywords: 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; périodes historiques; régions géographiques; thématiques

Chair à canons: Photographie, discours, féminisme - Solomon-Godeau, Abigail; Poupard, Laure; Jones, Julie (Éditions Textuel, 2016)
a 4e de couverture indique : [L'auteure] est aujourd'hui l'une des plus importantes théoriciennes de la photographie. Historienne de l'art, critique et professeur émérite à l'université de Californie à Santa Barbara, ses travaux portent principalement sur la théorie du genre, les études féministes, la culture visuelle en France au XIXe siècle, l'histoire de la photographie et l'art contemporain. ... le présent recueil réunit pour la première fois en langue française un ensemble d'essais parmi les plus significatifs de cette auteure majeure. ... l'ouvrage propose une première partie sur les discours de l'histoire de la photographie, une deuxième sur les pratiques documentaires et une troisième sur la représentation du féminin.
Section: 1 v. (252 p.) : couv. illustrations ; 21 cm
Keywords: 1900-1999; Photographie documentaire; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire de la photographie; histoire et politique; photographie; premier cycle; périodes historiques; représentation des femme*; thématiques

Impact féministe sur l'art actuel: La Centrale à 40 ans = Feminist impact on contemporary art : La Centrale at 40 - Burisch, Nicole (La Centrale Galerie Powerhouse, 2015)
"Publication, célébrant les 40 ans d'engagement de la Centrale qui se voue au développement de l'histoire des pratiques artistiques féministes et soutient la visibilité d'artistes et d'initiatives moins ou peu représenté-es auprès des institutions culturelles établies"–Page 40.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; périodes historiques; québec; régions géographiques; sex1911; thématiques

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Histoire de l'art d'un nouveau genre - Larue, Anne; Nachtergael, Magali (Max Milo, 2014)
''L'art a-t-il un genre ? Aujourd'hui encore le discours de l'histoire de l'art s'écrit essentiellement au masculin. On dirait que les femmes n'ont jamais pris part à ce processus, que l'art exige encore et toujours une performance liée à l'idée de masculinité. Adoptant le point de vue des femmes et s'appuyant sur des recherches en histoire de l'art, ce livre réévalue leur place et leur rôle dans la fabrique des arts. Il offre une large fresque (de - 42000 à l'époque contemporaine) où femmes et hommes dialoguent ensemble pour reconstruire notre mémoire culturelle d'une manière plus égalitaire, équilibrée et donc plus solide, tout en tenant compte des tensions de genre qui s'impriment dans le discours. Il offre également une riche iconographie, dont certaines oeuvres que vous n'avez encore jamais vues de votre vie !''– Site de l'éditeur.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiquité; approches et analyses; arts; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; rapports sociaux de sexe; thématiques

Les filles en série: des Barbies aux Pussy Riot - Delvaux, Martine (Les éditions du remue-ménage, 2013)
Des corps féminins en rangées, qui se meuvent en synchronie. Ils ne se distinguent que par le détail d’un vêtement, d’une courbe, d’une teinte de cheveux. Les filles en série créent l’illusion de la perfection. Ce sont des filles-machines, filles-marchandises, filles-ornements. Toutes reproduites mécaniquement par l’usine ordinaire de la misogynie. Les filles sont des filles parce qu’elles sont en série. Mais la figure des filles en série est double: à la fois serial girls et serial killers de l’identité qu’on cherche à leur imposer. Entre aliénation et contestation, les filles en série résistent à leur chosification, cassent le party, libèrent la poupée et se mettent à courir. Cet essai percutant, paru pour la première fois en 2013, se déploie comme une chaîne qui se fait et se défait, depuis les Cariatides jusqu’aux Pussy Riot. Dans cette édition revue et augmentée, Martine Delvaux s’attaque à la blancheur des filles en série et analyse de nouvelles formes de résistance investies par les ballerines, les survivantes d’agressions et Beyoncé.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem3500; fem7000; histoire de l'art; histoire et politique; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit3220; militance; premier cycle; systèmes d'oppressions; thématiques; études culturelles; études littéraires

La rébellion du deuxième sexe : l'histoire de l'art au crible des théories féministes anglo-américaines (1970-2000) - Dumont, Fabienne (Les presses du réel, 2011)
Cette anthologie, la première du genre en langue française, retrace l'histoire complexe de quarante années de théories féministes anglo-américaines en histoire de l'art, à partir d'exemples détaillés et emblématiques. Les premiers écrits abordent l'histoire des pionnières de cette théorisation féministe, avec des écrits de Lucy Lippard, une analyse rétrospective des caractéristiques du mouvement californien des années 1970 ou des réceptions polémiques de The Dinner Party. Une seconde partie est consacrée à des textes qui s'attachent à une relecture de l'histoire de l'art des siècles passés, que ce soit le point de vue de Griselda Pollock, des « vieilles maîtresses » à une théorisation des espaces de la féminité, ou des approches plus marxistes du travail des artistes. Le troisième volet regroupe de nouvelles perspectives : l'analyse des masculinités à l'époque moderne et dans les performances des années 1960-1970, puis une approche des problématiques spécifiques aux artistes de couleurs, notamment afro-américaines. Enfin, deux études permettent de faire le point sur le développement postféministe en art et les questions queer. Cette sélection, issue d'un vaste répertoire, permet d'aborder les différentes conceptions théoriques des études féministes, de genre et queer en art qui se sont succédées et répondues des années 1970 aux années 2000.
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; amériques; anthologie; approches et analyses; cours; discipline; europe; fem1000; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; thématiques; états-unis

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Number: 3
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

Art et féminisme - Reckitt, Helena; Phelan, Peggy; Reckitt, Helena; Phelan, Peggy (Phaidon, 2011)
Depuis la fin des années 1960, le mouvement féministe a été à l'origine d'innovations, à la fois théoriques et pratiques, qui figurent parmi les plus intéressantes de l'art contemporain. Par ailleurs, certains succès politiques du mouvement féministe ont été obtenus grâce aux artistes, qui ont proposé de nouvelles manières d'envisager les domaines privé et public, l'objet de l'art et son sujet. En soulignant la différence des sexes, le courant féministe a aussi attiré l'attention sur le rôle de l'âge, de la classe sociale, de la race et de la sexualité dans la création artistique et dans sa réception. À la fois critiques et actrices du monde de l'art, les artistes féministes ont donné un nouvel élan à l'art considéré comme démarche à la fois politique et esthétique. Cet ouvrage, conçu par Helena Reckitt, présente les expériences, les idées et les démarches actuelles d'artistes majeures, et met en évidence le lien existant entre les différentes générations d'artistes. L'essai de Peggy Phelan, théoricienne de l'art et de la performance, jette un regard original sur les interprétations classiques de l'art des femmes et propose de nouvelles clés pour comprendre les rapports mouvants entre idées et idéaux du féminisme et pratiques artistiques.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques; théorie de l'art

Mettre l'amitié au premier plan : passés et futurs féministes - Roseneil, Sasha (Nouvelles Questions Féministes, 2011)
L'amitié est un champ d'études peu exploré et cependant d'importance vitale pour les études genre et féministes. En revisitant l'histoire des écrits féministes sur les amitiés entre femmes, l'article explore l'importance qui est donnée à l'amitié par les premières générations de féministes tout au long du XXe siècle. En se concentrant sur les considérations polémiques, théoriques et empiriques à l'égard de l'amitié, l'article suggère que l'amitié a été historiquement fondamentale pour les politiques, les identités et les communautés féministes. Il conclut par un argument en faveur de la place centrale de l'amitié - avec le même sexe, hommes et femmes, mais aussi entre les sexes - dans les programmes de recherche féministes, aujourd'hui et dans l'avenir. Le prisme de l'amitié conduit à une remise en question radicale de l'hétéronormativité des sciences sociales, et attire notre attention sur les façons dont la vie intime a été reconfigurée au début du XXIe siècle.
https://www.jstor.org/stable/41346017 Traduction de : Sasha Roseneil (2006). « Foregrounding Friendship : Feminist Pasts, Feminist Futures ». In Kathy Davis, Mary Evans & Judith Lorber (Éds) Handbook of Gender Women’s Studies, (pp. 322-341). Londres : SAGE Publications.
Keywords: 1900-1999; amitié; approches et analyses; care; cours; cycles supérieurs; discipline; fem7000; genre; histoire de l'art; histoire et politique; hétéronormativité; hétérosexisme; intimité; lesbianisme; littérature française; littérature lesbienne; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Femmes artistes du XXe siècle au Québec: œuvres du Muséee national des beaux-arts du Québec - Musée national des beaux-arts du Québec.; Trépanier, Esther (Musée national des beaux-arts du Québec, 2010)
Cet ouvrage, abondamment illustré d’œuvres tirées de la collection du Musée national des beaux-arts du Québec, constitue un hommage sans précédent à une centaine de femmes qui ont contribué à la vitalité de l’art québécois du XX e siècle. Le premier chapitre, intitulé La conquête d’un espace, 1900-1965 , est consacré aux premières décennies du siècle, alors que le second, L’éclatement des frontières, 1965-2000 , embrasse la période contemporaine. Enfin, une troisième section en forme de dictionnaire présente des notices biographiques sur les 100 artistes retenues. Ce livre est le premier titre de la collection « Arts du Québec », qui veut ouvrir de nouvelles perspectives sur l’art d’ici en explorant l’histoire de l’art québécois dans toute sa diversité, tout en convoquant des dimensions sociologiques, thématiques ou esthétiques inédites.
Keywords: 1900-1999; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

elles@centrepompidou Une nouvelle histoire ? - St-Gelais, Thérèse (Esse, 2010)
Commentaire de l'exposition elles@centre pompidou, Artistes femmes dans la collection du Musée national d’art moderne, centre de création industrielle qui eut lieu du 27 mai 2009 - 21 févr. 2011 au centre Pompidou à Paris.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; ressource en ligne; sofia; thématiques

Art et politique: nouvelles formes d'engagement artistique au Québec - Lamoureux, Ève (Éditions Écosociété, 2009)
Les artistes contemporains délaissent les grandes luttes communes, les partis politiques, et acceptent les subventions de l'État. Ils refusent les étiquettes et se moquent du mythe de l'artiste guidant le peuple. Quand l'oeuvre d'art devient fragments, mouvement, quand son sens est ouvert et dépend de l'expérience du spectateur, quelle est son action sur le monde? Peut-on encore croire à sa portée politique? Les nostalgiques pleurent la disparition de l'art engagé. Pour Ève Lamoureux, l'art engagé n'a jamais cédé; il résiste d'une autre manière, à un autre pouvoir, sur d'autres terrains. Exit la division entre l'art pour l'art et l'art au service d'une idée. Exit la conception avant-gardiste militante de l'art engagé. L'engagement actuel passe par une action micropolitique multiforme, une création soucieuse de l'Autre, à la fois autonome et collective, misant sur le processus et la participation. Ainsi, l'auteure nous montre de quelle façon l'art apporte une nouvelle définition de l'engagement politique. Cet essai analyse la démarche d'artistes québécois comme l'ATSA, BGL, Doyon/Demers, Danyèle Alain, Sylvie Cotton, Nicole Jolicoeur, Devora Neumark, Alain-Martin Richard, Jean-Claude St-Hilaire et Raphaëlle de Groot. En prolongeant, sur le plan théorique, des créations souvent performatives et éphémères (décors, manifestations, dialogues, oeuvres à compléter soi-même, etc.), ce livre les situe dans l'histoire récente de l'art et met en lumière leur dimension politique.
Keywords: 1900-1999; 2000 à aujourd'hui; amériques; approches et analyses; art engagé; arts; canada; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Esquisse d'une épistémologie de la théorisation féministe en art - Dumont, Fabienne; Sofio, Séverine (Cahiers du Genre, 2007)
Résumé Les recherches dans et sur le domaine de la théorisation féministe en art étant peu développées en France, nous avons choisi de revenir, dans cet article, sur les contextes d’émergence de cette théorisation, depuis les premières réflexions sur la place des femmes dans le monde artistique jusqu’aux tentatives d’articuler pratiques esthétiques et expression politique, sous l’influence du mouvement féministe. Dans un second temps, nous tentons d’établir une typologie des thématiques que les questionnements féministes ont contribué à renouveler tant dans le domaine de l’art que, plus largement, dans celui de la réflexion sur la création artistique, des années 1980 à aujourd’hui.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sex1911; thématiques; théorie de l'art; épistémologies féministes

Femmes artistes/artistes femmes: Paris, de 1880 à nos jours - Gonnard, Catherine; Lebovici, E. (Hazan, 2007)
L'histoire de l'accès des femmes à la pratique artistique depuis la fin du XIXe siècle. Etudie l'ouverture des académies parisiennes aux femmes, les femmes dans les avant-gardes du XXe siècle (fauvisme, cubisme, surréalisme, etc.), leur place dans la danse, la photographie, les arts décoratifs et le cinéma, les réseaux et galeries réunissant des femmes artistes, le féminisme dans l'art, etc.
OCLC: ocn173239653
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; paris; premier cycle; pédagogie; périodes historiques; régions géographiques; thématiques; travail

Global feminisms: new directions in contemporary art - Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center.; Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center. (Merrell ;, 2007)
Catalogue for the exhibition Global Feminisms, that took place at the Brooklyn Museum in 2007. The first international exhibition exclusively dedicated to feminist art from 1990 to the present. The show consists of work by approximately eighty women artists from around the world and includes work in all media—painting, sculpture, photography, film, video, installation, and performance. Its goal is not only to showcase a large sampling of contemporary feminist art from a global perspective but also to move beyond the specifically Western brand of feminism that has been perceived as the dominant voice of feminist and artistic practice since the early 1970s.This exhibition is arranged thematically and features the work of important emerging and mid-career artists.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Reclaiming female agency: feminist art history after postmodernism - Broude, Norma..; Garrard, Mary D.; Broude, Norma; Garrard, Mary D. (University of California Press, 2005)
This volume is the third in an influential series of anthologies by editors Norma Broude and Mary D. Garrard that challenge art history from a feminist perspective. Following their Feminism and Art History: Questioning the Litany (1982) and The Expanding Discourse: Feminism and Art History (1992), this new volume identifies female agency as a central theme of recent feminist scholarship. Framed by a lucid and stimulating critical introduction, twenty-three essays on artists and issues from the Renaissance to the present, written in the 1990s and after, offer a nuanced critique of the poststructuralist premises of 1980s feminist art history.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; thématiques

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Number: 1
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Féminin pluriel et féminismes en arts visuels au Québec - Boileau, Julia (Esse, 2004)
Il y a plus de 20 ans, en tant qu’historienne de l’art, j’avais posé la question à savoir si l’apport des femmes en art contemporain allait changer quelque chose à la pratique artistique et comment, de même qu’à la pratique de la critique et de l’histoire de l’art1. Ce qui suit est une évocation des principaux questionnements que l’art des femmes et les féminismes en art ont amenés au sein de l’art contemporain. La pratique de l’art mais aussi les pratiques muséologiques ont-elles été affectées par l’arrivée en nombre des femmes sur la scène de l’art moderne et contemporain ? La question des femmes recèle-t-elle encore une pertinence dans le monde de l’art contemporain d’aujourd’hui ?
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; art contemporain; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Féminin pluriel et féminismes en arts visuels au Québec - Arbour, Rose Marie (Esse arts + avis, 2004)
Publisher: Esse arts + opinions
Keywords: amériques; art contemporain; arts visuels et médiatiques; cours; discipline; fem1000; femmes* artistes; histoire de l'art; histoire et politique; premier cycle; québec; ressource en ligne; régions géographiques; thématiques

Les femmes dans l'art: qu'est-ce que les femmes ont apporté à l'art? - Bonnet, Marie-Jo (La Martinière, 2004)
Analyse l'évolution du statut de la femme dans l'art et tente de savoir ce qu'elles ont transmis à travers leurs oeuvres, du féminin, du masculin, de la souffrance et de la jouissance.
Keywords: 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Nouvelles sources et nouvelles méthodologies de recherche dans les études sur les femmes - Leduc, Guyonne (Harmattan, 2004)
Extrait de la couverture : "Etendue d'une information véritablement européenne, ouverture, multiplicité des apporches, diversités des points de vue et des regards croisés composent un ensemble touffu, foisonnant et stimulant. Ce qui frappe d'abord, c'est l'ampleur des perspectives spatiales - de la Russie aux Etats-Unis, de l'Angleterre, dominante, à l'Italie et à l'Espagne - et tout autant temporelles : du Moyen Age au féminisme actuel de Susan fAludi. Grâce à la variété culturelle des auteurs, on respire hors des confins de l'hexagone. Il y a, dans ce livre, une volonté critique, un désir de lutter contre les idées reçues, notamment en ce qui concerne la chronologie de l'histoire des femmes, la revalorisation d'une époque moderne qu'on ne cesse de redécouvrir et l'impact des Révolutions, qu'on dévaluerait plutôt. Cet ouvrage fournit, en outre, un panorama comparatif des recherches littéraires sur les femmes en Europe, un état des lieux particulièrement exhaustif pour la Grande-Bretagne, mais aussi pour l'Allemagne, l'Italie et l'Espagne. Instrument de travail, il offre un bilan réconfortant. On mesure à quel point ce type d'études s'est développé depuis trente ans. La mise en perspective européemme de ce livre est salutaire... De ce point de vue, ce livre sonne comme un avertissement et une invitations. Signe d'aviditlé, il dit l'urgence de l'ouverture et la nécessité de dépasser les frontières pour confluer vers l'objet commun (extraits de la préface de Michelle Perrot)"
Keywords: allemagne; amériques; arts; cours; discipline; espagne; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; italie; premier cycle; royaume-uni; russie; régions géographiques; thématiques; écriture des femmes*; états-unis

Caught in the act: an anthology of performance art by Canadian women - Mars, Tanya; Householder, Johanna; Mars, Tanya; Householder, Johanna (YYZ Books, 2004)
This indispensable anthology gives readers access to an important and under-recognized subject in recent Canadian art history. Edited by two seminal Canadian performance artists, this book focuses on the 70s and 80s; a time when women made a big and noisy impact. Full of sass and insight, this essential collection is part survey, part critical discourse, and part reference book, containing five critical essays, thirty-four artist's profiles, and an extensive bibliography.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; art contemporain; arts; canada; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Amazons of the avant-garde: Alexandra Exter ... [et al.] - Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin.; Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin. (Solomon R. Guggenheim Museum, 2000)
Amazons of the Avant-Garde presents work by six Russian women who contributed to the development of modern art in the first quarter of the 20th century: Alexandra Exter, Natalia Goncharova, Liubov Popova, Olga Rozanova, Varvara Stepanova, and Nadezhda Udaltsova. The catalogue includes several essays that discuss the hindrances and influences affecting women in Russian avant-garde art circles. In addition, each artist featured in the exhibition is individually discussed at length, along with biographical timelines and excerpts of their writings from letters and publications. Color reproductions of the works in the exhibition accompany the essays to form a cohesive illustration of the art world in Russia during the first decades of the 20th century and the women who changed the aesthetic canons of their time. Alexandra Exter – Natalia Goncharova – Liubov Popova – Olga Rozanova – Varvara Stepanova – Nadezhda Udaltsova
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; russie; régions géographiques; thématiques

Femmes & art au XXe siècle: le temps des défis - Dumas, Marie-Hélène (Lunes, 2000)
Que cela soit dans les plus prestigieuses expositions ou bien dans les livres consacrés à l'art, le très faible nombre de femmes représentées ou citées - en tous les cas en France - laisse perplexe. Pourtant, les femmes ont toutes les qualités pour être reconnues comme de grands artistés. Le débat autour du statut de la <> demeure donc plus que jamais d'actualité. Cet ouvrage pose la question de la reconnaissance des femmes dans le milieu artistique tout au long du XXe siècle. Par une mise en perspective historique - car l'art n'est pas en dehors de la société - il analyse comment les femmes ont participé à la création et au développement de différents mouvements (constructivisme, dadaïsme, surréalisme, art féministe. Fluxus, ou encore le cyber-art). Il permet également de mieux comprendre les démarches d'un grand nombre d'artistes, certaines très connues comme ou Yoko Ono ou Sophie Calle, ou ne devant surtout pas être oubliées comme Hannah Höch, ou Natalia Gontcharova. Ce livre vous invite à découvrir la richesse créatrice dont ont témoigné de nombreuses femmes de tous pays tout au long du XXe siècle, mais qui demeure trop souvent invisible.
Le texte suivant : Collin, Françoise. (2000). La sortie de l’innocence, 175-189 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sciences humaines; sex1911; thématiques

L'art des femmes - Institut de recherches et d'études féministes (FéminÉtudes, 2000)
Cette publication du début du millénaire porte sur les femmes artistes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Discipline en libre accès : https://iref.uqam.ca/feminetudes/vol-5-no-1-2000-femmes-artistes/
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; arts visuels et médiatiques; discipline; féminétudes; histoire de l'art; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Section: 224 pages : illustrations ; 29 cm
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Jacqueline Chambon, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Première publication: 1991 Titre original: Women, Art, and Power, and Other Essays.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Première publication : 1991
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." – Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Section: 239 p. : ill. ; 24 cm
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
http://catalogue.bnf.fr/ark:/12148/cb349656237
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Pandora Press, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. –back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." –From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Section: 99 p.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

Une Histoire des femmes est-elle possible? - Perrot, Michelle (Rivages, 1984)
Les femmes ont-elles une histoire ? Pourquoi cette histoire n’a-t-elle pas été écrite dans le passé et pourquoi se développe-t-elle depuis une dizaine d’années ? De quelles sources dispose-t-on à cet égard et cette démarche implique-t-elle des méthodes particulières ? Que signifient « mémoire », « culture », « pouvoir » des femmes ? La catégorie de sexe est-elle, comme celle des âges, une variable historique issue des nouveaux classements induits par le développement de l’individualisme ? ou quelque chose de plus ? Voilà quelques unes des questions abordées dans ce livre qui prend en compte le changement de direction du regard historique lorsque l’on pose la question du rapport des sexes comme central. Avec la participation d’Alain Corbin, Arlette Farge, Agnès Fine, Catherine Fouquet, Geneviève Fraisse, Christiane Klapisch, Yvonne Knibiehler, Michelle Perrot, Elisabeth Ravoux-Rallo, Jacques Revel, Anne Roche, Pauline Schmitt-Pantel, Sylvie Van de Casteele, Danièle Voldman.
Keywords: arts; cours; discipline; france; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland Pub, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Section: 64 p. : ill. (certaines en coul.)
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

From the center: feminist essays on women's art - Lippard, Lucy R. (E.P. Dutton, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper & Row, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

MOOC Elles font l'art - St-Gelais, Thérèse; Ziebinska-Lewandowska, Karolina; Lascault, Catherine (FUN MOOC)
Après le succès de sa première diffusion avec plus de 41 000 inscriptions, le MOOC "Elles font l'art" réouvre ! Ce cours en ligne gratuit et ouvert à toutes et tous, constitué de vidéos, de quiz et d’activités, se consacre aux femmes artistes de 1900 à nos jours. Plasticiennes, peintres, photographes, vidéastes ou performeuses de toutes nationalités, elles ont fait ou font encore l’art des 20e et 21e siècles. A travers un parcours chronologique, nous vous invitons à découvrir une autre histoire de l’art moderne et contemporain dédiée aux créatrices. C'est une nouvelle manière pour le Centre Pompidou d'affirmer avec force son engagement auprès des femmes, et en faveur de l’égalité entre les genres.
Keywords: 1900-1999; 2000 à aujourd'hui; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; formations; har4600; histoire de l'art; histoire et politique; outils; premier cycle; périodes historiques; thématiques